2016
DOI: 10.1590/0103-8478cr20150445
|View full text |Cite
|
Sign up to set email alerts
|

Economic and soil quality indicators in soybean crops grown under integrated crop-livestock and winter-grain cultivation systems

Abstract: This study aimed to evaluate the relationship between economic indicators of soybean crops (Glycine max L.) cultivated with Crop-Livestock Integration (CLI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It was present in 15% of the reviewed studies. From this total, half (seven out of 14) have assessed several taxa and the other half have focused on a specific taxon, such as springtails (Machado et al, 2019; Oliveira Filho et al., 2016; Ortiz et al., 2019; Santos, et al., 2018), ants (Crepaldi et al., 2014), beetles (Pompeo et al., 2017) and earthworms (Simioni et al., 2016). Springtail morphotyping, an alternative to traditional taxonomy, was proven to be an efficient tool to assess soil biological quality in integrated crop–livestock systems.…”
Section: Resultsmentioning
confidence: 99%
“…It was present in 15% of the reviewed studies. From this total, half (seven out of 14) have assessed several taxa and the other half have focused on a specific taxon, such as springtails (Machado et al, 2019; Oliveira Filho et al., 2016; Ortiz et al., 2019; Santos, et al., 2018), ants (Crepaldi et al., 2014), beetles (Pompeo et al., 2017) and earthworms (Simioni et al., 2016). Springtail morphotyping, an alternative to traditional taxonomy, was proven to be an efficient tool to assess soil biological quality in integrated crop–livestock systems.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the presence of phosphorus and potassium, even in soils with low organic matter, results in good grain yield (BEUTLER et al, 2016), as observed in the Internal Coastal Plain. In addition, soil macroporosity is an important physical attribute in soil pore distribution analysis (SIMIONI et al, 2016). With greater porosity the nutrients are more accessible to plants.…”
Section: Resultsmentioning
confidence: 99%